The gay book of days : an evocatively illustrated who's who of who is, was, may have been, probably was, and almost certainly seems to have been gay during the past 5000 years - Greif, Martin (New York : Carol Publishing Group, 1989)
Fonds Suzan Daniel (FSD)
Engels
Monografie